Cellular Automata and Discrete Complex Systems 23rd IFIP WG 1.5 International Workshop, AUTOMATA 2017, Milan, Italy, June 7-9, 2017, Proceedings - Dennunzio, Alberto; Formenti, Enrico; Manzoni, Luca.; Porreca, Antonio E.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This volume constitutes the thoroughly refereed proceedings of the 23rd IFIP WG 1.5 International Workshop on Cellular Automata and Discrete Complex Systems, AUTOMATA 2017, held in Milan, Italy, in June 2017. The 14 full papers presented together with one full-length invited paper and 2 invited talk abstracts were carefully reviewed and selected from a total of 28 submissions. The papers feature research on correlated models of automata. The topics include aspects and features of such models: dynamics; topological, ergodic, and algebraic aspects; algorithmic and complexity issues; emergent properties; formal languages; symbolic dynamics; tilings; models of parallelism and distributed systems; timing schemes; synchronous versus asynchronous models; phenomenological descriptions; scientific modelling; practical applications. .
Keywords: Computer science; Algorithms; Computer simulation; 9; Computer science -- Mathematics; Mathematical statistics; Machine theory; Theory of Computation; Algorithms; Computer Modelling; Computer Communication Networks; Probability and Statistics in Computer Science; Formal Languages and Automata Theory